(untitled) (Journal of Imam Al-Kadhim College, 2025)
In light of the deteriorating social and political conditions that the Islamic world witnessed during the 3rd and 4th centuries of the Hijra, a group known as (The Brothers of "Ikhwan al-safa wa khulan al-wfa") emerged. This group surrounded itself with an aura of secrecy and confidentiality. It appears to have been numerous and composed of individuals from various strata of society. However, there is insufficient historical evidence regarding the origin of this group, the number of its members, its prominent figures, and its goals. As a result, several theories emerged to determine the identity, direction, and doctrine of this group. The group also established an internal system, and scholars and researchers have disagreed on the objective and purpose behind the formation and organization of the Brothers of Purity. Perhaps the reason for this disagreement lies in the diversity of sciences and knowledge presented in their epistles, which covered various fields of knowledge at that time. As for the epistles attributed to this group, they did not carry the names of their authors or author. This led to significant differences regarding the identity of the author or authors of these letters, their identities, and their doctrinal affiliations. Consequently, several theories have been put forward by various writers and researchers, both Muslim and non-Muslim, to determine the identity of the authors of the Epistles of the Brothers of Purity. Disagreement also arose regarding the time of the composition of these epistles. Numerous studies have emerged addressing the content of these epistles, their number, their structure, and their editions. The research also pointed out some formal and substantive issues related to these epistles.